Bioinspired Conyza bonariensis-mediated ZnO/rGO NCs for effective degradation of toxic compounds under visible-light irradiation - Rohit S. Madankar; Pavan Bhilkar; Mohammad Raish; Ajay Potbhare; Małgorzata Norek; Subhash Somkuwar; Ankita Daddemal-Chaudhary; Aniruddha Mondal; Ratiram Chaudhary (Scientific Reports)
Abstract This study reports a green, cost-effective synthesis of ZnO/rGO nanocomposites (NCs) using Conyza bonariensis leaf extract as a novel bio-reducing agent. The nanocomposites were prepared via a simple hydrothermal method. Extensive characterization techniques including XRD, FT-IR, EDS, UV-DRS, XPS, BET, SEM, TEM, and AFM were employed to evaluate the crystallite size, phase structure, chemical composition, surface morphology, porosity, and particle size of the synthesized material. XRD analysis confirmed the formation of a hexagonal wurtzite ZnO phase with an average crystallite size of approximately 17.22 nm, calculated using the Debye–Scherrer equation. SEM revealed a distinctive “tuberose flower”-like morphology of ZnO particles distributed on the reduced graphene oxide (rGO) sheets, with flower diameters ranging from 1 to 2 μm and petal widths of 40–70 nm. Further, TEM supported the uniform distribution of ZnO tubular petals on graphene nanosheets. BET analysis demonstrated the mesoporous nature of NCs. Remarkably, the bioinspired ZnO/rGO NCs exhibited excellent photocatalytic activity under visible-light irradiation, effectively degrading industrial dyes such as Congo red (CR), Methylene blue (MB), and Thymol blue (TB). The enhanced photocatalytic performance is attributed to the nanocomposites’ unique scaffold-like architecture, increased light absorption, and efficient charge separation.